Pseudomonas daroniae sp. nov. and Pseudomonas dryadis sp. nov., isolated from pedunculate oak affected by acute oak decline in the UK. Issue 11 (17th October 2019) - Bueno-Gonzalez, Victoria; Brady, Carrie; Denman, Sandra; Plummer, Sarah; Allainguillaume, Joel; Arnold, Dawn
Abstract : Twenty-two cream-coloured bacterial strains were isolated from oak trees affected by acute oak decline (AOD) in Southern England. Isolates were Gram-negative, motile, slightly curved rods, aerobic, non-spore-forming, catalase positive and oxidase positive. 16S rRNA gene sequence analysis placed the strains in two separate phylogenetic clusters in the Pseudomonas straminea group, with Pseudomonas flavescens as the closest phylogenetic relative. Multilocus sequence analyses of the gyrB, rpoD and rpoB genes supported the delineation of the strains into two separate taxa, which could be differentiated phenotypically and chemotaxonomically from each other, and their closest relatives. Average nucleotide identity and in silico DNA–DNA hybridization values revealed percentages of genome similarity below the species threshold (95 and 70 %, respectively) between the two taxa and the closest relatives, confirming their novel species status. Therefore, on the basis of this polyphasic approach we propose two novel Pseudomonas species, Pseudomonas daroniae sp. nov. (type strain FRB 228 T =LMG 31087 T =NCPPB 4672 T ) and Pseudomonas dryadis sp. nov. (type strain FRB 230 T =LMG 31087 T =NCPPB 4673 T ).